Фабрика поломанных игрушек - Фотич Гера (Любимый детектив, 2021)
Экземпляры: Камская библиотека (20220606) / Инвентарный номер: 14502 / Цена: / Сис.шифр: 84(2Рос=411.2)6 / Авт.знак: Ф 81 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=411.2)6